SOSIALISASI USIA DINI LEMBAGA BIMBINGAN BELAJAR (Studi Kasus biMBA-AIUEO Ardath Kota Pekanbaru) - Rahmah M, Zesty Laila; Asriwandari, Hesti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Bimba-Aiueo is a non-formal educational institutions early age (3-6 years) who were in the shade of the Indonesian Child Education Foundation (YPAI). Bimba-Aiueo not a tutoring but organizers of a guidance unit interest in reading and learning of children, especially young children. Early childhood is a group of children who are in the process of growth and development is untuk.Penelitian aims to determine how the process of learning and playing in Bimba-Aiueo Ardath Pekanbaru, to determine the value of planting in Bimba-Aiueo Ardath. The theory used in this research is the theory of socialization. Socialization is a learning process and appreciate the individual to megenal norms and social values, causing the formation of attitudes to behave in accordance with the guidance or the behavior of its people.Keywords: Bimba-Aiueo, Childhood, socialization